Immunoregulation mechanism of Treg cells in anti-GBM glomerulonephritis model of mice - ZHOU Huan; ZHANG Xin; HE Yong; PENG Qing-ping; WANG Xiao-hui (Linchuang shenzangbing zazhi)
Objective To explore the immunoregulation mechanism of Treg cells in anti-GBM glomerulonephritis model of mice,and provide theoretical basis for early intervention of immune response and alleviating pathologic damage. Methods C57BL/6 mice were randomly divided into nephritic group and normal control group. The anti-GBM glomerulonephritis model was established in the mice of the nephritic group. At different time points of 7th,14 th,21st and 28 th day,mice were sacrificed. The serum was collected,and creatinine( SCr),blood urea nitrogen( BUN),urine albumin and albumin-to-creatinine ratio( ACR) were tested. Renal pathological changes were observed. Treg cells in the spleen were examined by fluorescence-activated cell sorting( FACS). Western blotting was used to detect the expression of Id3 and Foxp3 protein in the renal tissues. Results The irregular thickening and breakage of GBM,glomerular mesangial cells,matrix proliferation,and crescent formation were observed in nephritic group. Immunofluorescence showed rabbit IgG and mouse IgG linearly deposited along the GBM in nephritic group. SCr,BUN,urine albumin and ACR increased significantly in nephritic group as compared with normal control group( P <0. 05). The anti-GBM glomerulonephritis model group of cells,and protein expression levels of relevant indicators show the law: FACS showed Th17 cells declined after increased,while Tregs increased significantly from 7th day( P < 0. 05 or P < 0. 01); The protein expression levels of Id3 and the transcription factors Foxp3 in anti-GBM glomerulonephritis group were increased significantly( P < 0. 05 or P < 0. 01). The expression levels of Id3 protein were positive correlated with the Tregs’ transcription factors. Conclusions In the immune process of anti-GBM nephritis,Treg plays an important role,which may be related to the transcriptional regulator Id3.